The gay and lesbian emancipation policy of the city of Amsterdam - Nijboer, Jeannette; Veeger, Margriet (Amsterdam: Communications Department of the city of Amsterdam, 1998)
"Jeannette Nijboer; Margriet Veeger Fonds Suzan Daniel (FSD)"